2016
DOI: 10.1159/000443935
|View full text |Cite
|
Sign up to set email alerts
|

Large Size Hemicraniectomy Reduces Early Herniation in Malignant Middle Cerebral Artery Infarction

Abstract: Background: Decompressive hemicraniectomy (DHC) reduces mortality and improves outcome after malignant middle cerebral artery infarction (MMI) but early in-hospital mortality remains high between 22 and 33%. Possibly, this circumstance is driven by cerebral herniation due to space-occupying brain swelling despite decompressive surgery. As the size of the removed bone flap may vary considerably between surgeons, a size too small could foster herniation. Here, we investigated the effect of the additional volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
(40 reference statements)
0
23
0
1
Order By: Relevance
“…DHC was performed in a standardized fashion and is described elsewhere in detail. 4,[7][8][9] Anesthesia was maintained with propofol and remifentanil. Mean arterial blood pressure was targeted between 70 and 80 mmHg.…”
Section: Surgery and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…DHC was performed in a standardized fashion and is described elsewhere in detail. 4,[7][8][9] Anesthesia was maintained with propofol and remifentanil. Mean arterial blood pressure was targeted between 70 and 80 mmHg.…”
Section: Surgery and Managementmentioning
confidence: 99%
“…So far, only few recent reports exist regarding outcome after DHC for treatment of MHS and most have rather focused on early or general mortality and not on longterm neurological disability as a primary outcome measure. 7,[12][13][14] Due to the far-reaching consequences of MHS, however, we believe that the decision to perform DHC should not just be based on the patient's chance to merely survive, but rather on the chance to reach an individually acceptable long-term outcome. 15 Since the purpose of our present study was not to confirm or reject the general indication for surgery like in the RCTs on MHS but rather to retrospectively identify non-modifiable risk factors for a higher degree of long-term neurological disability following DHC, we selected an mRS cut-off between 3 and 4, which according to recent surveys, most patients and physicians would consider acceptable.…”
Section: Outcome After Decompressive Surgery For Treatment Of Mhsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported benefits and limitations of DC and compared surgical effects according to causative diseases 15,24,39) . Some reports insist that DC should be as large as possible or bone fragment to be removed should be at least 12×15 cm in size or have a diameter of 15 cm 8,29,31) .…”
Section: Discussionmentioning
confidence: 99%
“…Dowiedziono związku pomiędzy średnicą wykonanej kraniektomii a objętością uzyskiwaną poprzez jej przeprowadzenie dla obrzękniętego mózgu oraz efektami leczenia. Wykazano ponadto, że wraz ze wzrostem średnicy kraniektomii, przy mniejszej wysokości wstawiania się mózgowia uzyskuje się większe, dodatkowe objętości [43,44,45]. Efekt ten ma niebagatelne znaczenie w przeciwdziałaniu powstawania miejscowych uszkodzeń kory na granicy otwarcia kostnego [46].…”
Section: Dyskusjaunclassified